2009
DOI: 10.1038/hdy.2009.8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hybrids in nature: application to oaks (Quercus suber and Q. ilex)

Abstract: Powerful and accurate detection of first-generation (F1) hybrids and backcrosses in nature is needed to achieve a better understanding of the function and dynamics of introgression. To document the frequency of ongoing interspecific gene exchange between two Mediterranean evergreen oaks, the cork oak (Quercus suber) and the holm oak (Q. ilex), we analyzed 1487 individuals originating from across the range of the two species using eight microsatellite loci and two Bayesian clustering approaches (implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
172
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(185 citation statements)
references
References 68 publications
12
172
0
1
Order By: Relevance
“…Oak species with similar reproductive strategies and overlapping geographic regions often hybridize in natural stands (Chybicki & Burczyk, 2010; Curtu, Gailing, & Finkeldey, 2007; Dodd & Afzal‐Rafii, 2004; Dumolin‐Lapègue, Démesure, Fineschi, Le Corre, & Petit, 1997; Dumolin‐Lapègue, Kremer, & Petit, 1999; Efrain Tovar‐Sanchez, 2004; Gerber et al., 2014; Hipp & Weber, 2008; Lexer, Kremer, & Petit, 2006; Moran, Willis, & Clark, 2012; Petit, 1993; Petit et al., 2004; Whittemore & Schaal, 1991). Morphological intermediacy, however, is an imperfect predictor of genetic admixture in oaks, making hybrids difficult to identify (Burgarella et al., 2009; Song, Deng, Hipp, & Li, 2015; Wei, Li, Zhang, & Liao, 2015). Moreover, multispecies hybrid zones are common in oaks and particularly difficult to study due to sampling issues and selection of adequate numbers of informative loci (Craft & Ashley, 2006; Dodd & Afzal‐Rafii, 2004; Peñaloza‐Ramírez et al., 2010; Sullivan, Owusu, Weber, Hipp, & Gailing, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Oak species with similar reproductive strategies and overlapping geographic regions often hybridize in natural stands (Chybicki & Burczyk, 2010; Curtu, Gailing, & Finkeldey, 2007; Dodd & Afzal‐Rafii, 2004; Dumolin‐Lapègue, Démesure, Fineschi, Le Corre, & Petit, 1997; Dumolin‐Lapègue, Kremer, & Petit, 1999; Efrain Tovar‐Sanchez, 2004; Gerber et al., 2014; Hipp & Weber, 2008; Lexer, Kremer, & Petit, 2006; Moran, Willis, & Clark, 2012; Petit, 1993; Petit et al., 2004; Whittemore & Schaal, 1991). Morphological intermediacy, however, is an imperfect predictor of genetic admixture in oaks, making hybrids difficult to identify (Burgarella et al., 2009; Song, Deng, Hipp, & Li, 2015; Wei, Li, Zhang, & Liao, 2015). Moreover, multispecies hybrid zones are common in oaks and particularly difficult to study due to sampling issues and selection of adequate numbers of informative loci (Craft & Ashley, 2006; Dodd & Afzal‐Rafii, 2004; Peñaloza‐Ramírez et al., 2010; Sullivan, Owusu, Weber, Hipp, & Gailing, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1 includes the expected values of q, the probability of an individual to belong to the Q. suber cluster, provided by STRUCTURE. This parameter can be used to detect hybrid individuals (Burgarella et al 2009) and is frequently considered a proxy of the contribution of one species to the genome. Burgarella et al (2009) reported a good performance of STRUCTURE and this set of markers for the detection of first generation hybrids and first backcrosses, in terms of efficiency and accuracy (sensu Vähä & Primmer 2006).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Nuclear molecular markers combined with Bayesian approaches have been used for the identification of hybrid individuals in populations, according to the posterior probability of each individual to belong to any of the parental species genetic clusters. This approach was applied by Burgarella et al (2009) in sympatric Q. ilex -Q. suber populations, estimating a current introgression rate of <2%. Later on, this procedure has been applied in studies for many other species, including animals (Neaves et al 2010, Bogdanowicz et al 2012, Malde et al 2017.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations